2000
DOI: 10.1155/dte.7.69
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Pneumothorax Associated With Lung and Pleural Metastases of Breast Cancer

Abstract: A rare case of bilateral pneumothorax in a 54-year-old woman with advanced breast cancer associated with lung and pleural metastases is presented. The patient was admitted to our hospital complaining of unexpected severe dyspnea. A chest X-ray showed bilateral pneumothorax associated with multiple lung metastases and pleural effusions, followed by immediate pleural drainage. Although air leak and effusions of the right lung were well controlled by the conservative management, massive air leaks of the left lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…4 It should be confirmed with the histopathological findings of the pulmonary and pleura cells. 2 In this case we did not do a histopathology procedure. Therefore, we were not sure if the pneumothorax occurred because of this pathophysiology.…”
Section: Case Report and Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…4 It should be confirmed with the histopathological findings of the pulmonary and pleura cells. 2 In this case we did not do a histopathology procedure. Therefore, we were not sure if the pneumothorax occurred because of this pathophysiology.…”
Section: Case Report and Discussionmentioning
confidence: 98%
“…Pneumothorax associated with lung metastasis is frequently provoked by treatment-induced necrosis of metastatic tumor. 2 There were a few reports of pneumothorax provoked by the treatment of lung metastases. Saito Y et al reported in a journal a similar case with a bilateral pneumothorax formation following chemotherapy of tounge cancer.…”
Section: Case Report and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of all spontaneous pneumothorax, only 1.3-1.9% of cases present with simultaneous bilateral spontaneous pneumothorax. MSSP has been reported in patients on radiation therapy, angiogenesis inhibitors, and pleural metastasis from breast carcinoma [8].…”
Section: Discussionmentioning
confidence: 99%